Avaliação de biomarcadores inflamatórios, dor e qualidade de vida em pacientes com câncer de cabeça e pescoço antes da terapia antineoplásica - Oliveira, Karine Gadioli de (2013)
The pain is a common symptom in patients with cancer, including those with head and neck cancer (HNC). This pain can affect physical functions, emotional states, and patients‟ quality of life (QoL). The HNC is the 6th most common cancer worldwide, accounting for approximately 6% of cancer cases. Therefore, the purpose of this study was to assess the pain and its impact on the QoL of HNC patients and the relationship among pain, proinflammatory cytokine tumor necrosis factor alpha (TNFα) and C - reactive protein (CRP). We interviewed 127 untreated patients with primary head and neck squamous cell carcinoma, and clinical data such as gender, age, tobacco and alcohol consumption, tumor location and tumor stage were obtained from medical records. The pain was measured using the item of “average pain” during the last 24 hours in the Brief Pain Inventory (BPI) questionnaire, and the QoL was assessed with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 (EORTC QLQ-C30) and the head and neck module (QLQ-H&N35). The EORTC QLQ-C30 scales revealed that the patients with a tumor in the early stages scored significantly higher in functioning scales. Conversely, the patients with advanced stage cancer scored significantly higher on the symptom scales. On the QLQ-H&N35 scales, the patients with advanced stage tumors had significantly higher scores on the symptom scales. The group of patients with moderate-severe pain indicated a greater impairment on the symptom scales. The TNFα serum (pg/mL) in patients with pain (12,85 ± 1,7) was higher when compared to the no pain group (11,53 ± 2,3) (p < 0,05) and the controls (11,1 ± 1,4) (p < 0,05). The RCP serum (mg/L) in patients with pain (11,25 ± 8,3) was also higher when compared to the no pain group (6,93 ± 3,6) (p < 0,01) and the controls (4,77 ± 2,2) (p < 0,05). These biomarkers may be of great importance in HNC pain and may be future targets for new drugs and result in a better pain management and QoL of these patients.